The Synergy between White Supremacist and Jihadist Violence in the Targeting of Religious Institutions - Celso, Anthony (Advances in Social Sciences Research Journal, 2020)
The 2019 Easter Islamic State (IS) attacks on Sri Lankan churches is seen by the government as retribution for a white nationalist attack on Christchurch New Zealand mosques. This article analyses the synergy between white nationalist and jihadi violence. It examines the growth of the Western extremist right as a response to economic globalization and the cultural-religious transformation of European and North American society. In part right-wing terrorism is a response to past jihadi attacks in the West and radicalized minority sub-communities within Europe’s large Muslim Diaspora population. Much like the left-right terrorist violence that convulsed Europe in the 1970’s we may be facing a destabilizing future of revenge attacks by jihadists and their far-right antagonists that target religious institutions and celebrations. This process results in a synergistic level of violence in which Jews are at the greatest risk for attacks.